Development of a novel smart scaffold for human skeletal muscle regeneration. (23rd July 2013) - Shah, Rishma; Knowles, Jonathan C.; Hunt, Nigel P.; Lewis, Mark P.
Abstract: Skeletal muscle defects are notoriously difficult to manage and the current methods used are associated with many limitations. Engineered skeletal muscle tissue has the potential to provide a solution that circumvents these disadvantages. Our previous work has identified a novel three‐dimensionally aligned degradable phosphate glass fibre scaffold that can support myoblast differentiation and maturation. This current study has further developed the scaffold by encasing the fibres within a collagen gel to produce a smart composite scaffold that provides key biomimetic cues and supports the formation of a tissue that may be implanted in vivo . The constructs formed were approximately 30 mm long and microscopic examination confirmed favourable unidirectional cell alignment. There was good cell survival, and gene expression studies demonstrated upregulation of the myogenic regulatory factors and developmental and adult myosin heavy chain isoforms indicating myofibre formation and maturation respectively. Compared with the three‐dimensional glass fibre scaffolds, the composite scaffolds had later gene upregulation, however, the use of collagen gels reinforced with degradable aligned glass fibres offers the opportunity to create a tissue analogue that can be easily manipulated. Furthermore, the glass fibre ends could support tendon/bone formation, and the channels formed as the fibres degrade could allow for vascular ingrowth. Copyright © 2013 John Wiley & Sons, Ltd.